Avaliação da informação fornecida ao paciente com doença pulmonar obstrutiva crônica sobre sua doença e tratamento no momento da alta - Morais, Letícia de Araújo (2016)
Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous and multifactorial disease that causes a huge impact on the patient and the health system, causing exaggerated high costs. This study has as aim to evaluate the provided information to patients with COPD about their disease and treatment at the time of hospital discharge. A cross-sectional descriptive study with hospitalized patients for COPD in three tertiary hospitals using a standardized document for evaluation of the discharge checklist proposed by the Global Initiative for Chronic Obstructive Pulmonary Disease, containing 7 items. Hospitals were divided into (Group A) with residency in pulmonology (RMP) and (Group B) without RMP. It was evaluated 54 patients with a mean age of 66,6 ± 11,4, 25 (46,2%) were male, 22 (40,7%) (Group A) and 32 (59,3%) (Group B). Items related to ensure effective pharmacological maintenance treatment (item 1), blood gas evaluation/measurement of SpO2 (item 2), reassessment of inhalation technique (item 4), and information relating to maintenance therapy (item 5) were respectively 79,6%, 96,3%, 70,3%, and 88,9% of information. Comorbidity management plan (item 3) 29,6%, information regarding the completion of antibiotic therapy/corticosteroid (item 6) 44,4% and following assurance specialist (item 7) 55,6%. There was statistical significance between hospitals for items 1, 4 and 7 (p = 0,002, p ˂ 0,001, and p ˂ 0,001, respectively), with better performance in the patients in Group A. This study revealed the need for attention to instructions regarding the length of treatment of corticosteroid/antibiotics and comorbidity management plan. The lack of specialized care reveals lower yields in check information provided to COPD patients at hospital discharge.